Strengthening elementary students' reading interest through picture stories in Bobo Magazine - Rufiati, Halimah; Rahmawati, Fitri Puji (Universitas Ahmad Dahlan, 2024)
This research aims to understand how illustrated stories in Bobo magazine can strengthen elementary school students' interest in reading. This research utilizes a descriptive qualitative approach using triangulation techniques, method triangulation, and data source triangulation. This research focuses on class III A students. This research will have an impact on MI Muhammadiyah Gonilan, in its efforts to become a better literacy school, especially for the early classes. The implementation goes through 4 stages, namely the reading and understanding stage, the results presentation stage, the discussion and question and answer stage, and the concluding and reflection stage. The results of this research reveal that Bobo magazine can strengthen students' interest in reading. This research shows a form of strengthening students' reading interest through the “Jam Berbicara” program. The conclusion that can be found in this research is that storytime activities through Bobo magazine every morning can attract students to continue reading books so that their interest in reading will increase. In this research, teachers play a role in fostering students' interest in reading through familiarization with reading activities.